Purposes and intentions of business entities in the civil-law relations system - Zaytseva, Natalia Viktorovna (International Journal of Psychosocial Rehabilitation, 2020)
Two subjective elements of legal relations are analyzed in the article: purposes and intentions of the parties and their value in different legal systems, questions about the ways of estimation of intention of the parties applied in the system of common law depending on the type of legal relations are considered. The question of the legal nature of the purpose in the civil turnover of the Russian Federation and the influence of the tax doctrine "business purpose" on the qualification of entrepreneurial activity is also studied. Research objective: to identify the significance of subjective elements of the transaction in different legal systems, to determine the impact of the purpose of the transaction on the qualification of legal communication and the consequences of the non-conformity of the purpose of the transaction with the intentions of the parties. Methods: empirical methods of comparison, interpretation as general scientific methods of cognition, descriptions were also used in private scientific methods: comparative legal and system analysis methods. Results: An analysis of the various legal approaches shows that legal systems based on formalism leave the intention and goals of subjects beyond the legal qualification, since the main confirmation of the will of the parties is a written contract. However, an obvious reluctance to assess subjective elements in civil law disappears when assessing the behavior of subjects for tax regulation purposes. And in this vein, the goals of the participants are subjected to excessively close scrutiny. Conclusions: One of the basic differences in legal systems is the approach of the judiciary in attempting to assess both the will of parties to civil law relations and its implementation, depending on it, the law and order has a set of mechanisms to enable such assessment. The common law system, built on the freedom of contract, allows parties to choose both the form of recording their legal relations and their content. Because of the wide dissemination of the oral form of the contract, the courts have established mechanisms and ways to assess the intentions and objectives of the parties, and in all cases the intentions and objectives are legal fact. Whereas in the continental legal system, the purpose is a determinant condition for a certain kind of legal consequences, but not for the emergence of legal relations in general.